Experimental study on the low-velocity impact response of inter-ply S2-glass/aramid woven fabric hybrid laminates. (August 2022) - Rezasefat, Mohammad; Gonzalez-Jimenez, A.; Ma, Dayou; Vescovini, Alessandro; Lomazzi, Luca; da Silva, Amanda A.X.; Amico, Sandro C.; Manes, Andrea
Abstract: This paper presents an experimental evaluation of the effect of hybridization and stacking sequence on the low-velocity impact response of aramid/S2-glass/epoxy hybrid laminates. Plain-weave Kevlar ®29 and satin S2-glass fabrics were used and the laminates were manufactured by vacuum infusion moulding. Eight laminate configurations were studied, including two single-fibre samples (pure aramid or pure S2-glass) and six interply hybrids. Low-velocity impact tests were performed with three different impact energies (19 J, 37 J, 72 J) and significant variations in impact behaviour were observed among the laminates. Response Surface Methodology (RSM) was employed to investigate the effect of hybridization on impact performance, focusing on greater absorbed energy and smaller back face deformation. Hybridization led to significant changes in failure morphology and the combination of aramid and S2-glass laminates enhanced the impact performance, especially for up to 49.5 J impact energy, while the pure S2-glass laminate performed better for higher impact energies. Highlights: Impact response of interply Aramid and S2-glass fabrics/epoxy hybrid laminates. LVI tests were performed on 8 configurations at three impact energies of 19, 37, and 72 J. Hybridization changed the failure pattern and improved the energy absorption. Laminate with an aramid ratio of 50% was identified as most desirable at 19 and 37 J impacts. Single fabric S2-glass laminate was more desirable at 72 J impact.